1996
DOI: 10.1159/000264336
|View full text |Cite
|
Sign up to set email alerts
|

Use of Three-Dimensional Ultrasound to Establish the Prenatal Diagnosis of Fryns Syndrome

Abstract: Three-dimensional (3D) imaging permits surface reconstructions that allow a better view of the appearance of organs. We report a case of a fetus with cystic hygroma diagnosed at 11 weeks of gestation, associated with a diaphragmatic hernia. With the 3D reconstruction, we examined the fetal face much more easily, which presented facial dysmorphology, retrognathia, macrostomia and a broad nasal bridge. The conjunctions of these pathological features and a normal karyotype allowed to establish a prenatal diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 8 publications
(10 reference statements)
0
14
0
Order By: Relevance
“…In particular, distal limb malformations, which seem to be a strong key to the diagnosis when associated with CDH, were not detected in prenatal diagnosis even in a tertiary center. By reviewing the 11 cases of the prenatal diagnosis of FS in the scientific literature, we found that most of them (eight) fell into the atypical group spectrum according to the diagnostic criteria proposed by Lin et al . having only two out of six required criteria based on the prenatal observation.…”
Section: Clinical Features Of the Five Cases In The Present Study Andmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, distal limb malformations, which seem to be a strong key to the diagnosis when associated with CDH, were not detected in prenatal diagnosis even in a tertiary center. By reviewing the 11 cases of the prenatal diagnosis of FS in the scientific literature, we found that most of them (eight) fell into the atypical group spectrum according to the diagnostic criteria proposed by Lin et al . having only two out of six required criteria based on the prenatal observation.…”
Section: Clinical Features Of the Five Cases In The Present Study Andmentioning
confidence: 99%
“…A very few cases (11) of prenatal diagnosis for FS have been reported since 1988. 1,[11][12][13][14][15][16][17] As far as we can tell, the prenatal phenotype of this condition has never been described in detail, and recent literature is lacking.…”
mentioning
confidence: 99%
“…9) with exquisite detail. [18][19][20][21][22] Detailed imaging of the yolk sac, omphalomesenteric duct, trunk and umbilical cord, head and face, spine, extremities, and even genitalia is possible. This imaging provides opportunities for earlier and improved diagnosis of fetal anomalies in the first trimester and may potentially limit the need for more-invasive imaging techniques such as embryofetoscopy.…”
Section: Clinical Applications: the First Trimestermentioning
confidence: 99%
“…Fryns (1995) suggested the association of prenatal overgrowth with Fryns syndrome. Van Wymersch et al (1996) reported the prenatal 3-D ultrasound reconstruction of the facial dysmorphism associated with Fryns syndrome. Cystic Figure 2-Craniofacial dysmorphism of the proband at birth hygroma or nuchal thickening has been noted to be an important sonographic marker for Fryns syndrome in addition to congenital diaphragmatic hernia (Bulas et al, 1992;Hösli et al, 1997;Sheffield et al, 1998).…”
mentioning
confidence: 99%